Engineered Cathode Buffer Layers for Highly Efficient Organic Solar Cells: A Review (Adv. Mater. Interfaces 19/2022). Issue 19 (4th July 2022) - Bishnoi, Swati; Datt, Ram; Arya, Sandeep; Gupta, Sonal; Gupta, Ramashanker; Tsoi, Wing Chung; Sharma, Shailesh N.; Patole, Shashikant P.; Gupta, Vinay
Abstract : Cathode Buffer Layers for Efficient Organic Solar Cells The cathode buffer layer (CBL) plays a fundamental role in organic solar cells (OSCs) fabrication. It minimizes charge‐carrier recombination losses and improves the OSCs' device performance parameters. It has been a critical pillar in the design of solar cells, as reviewed in article number 2101693 by Swati Bishnoi, Vinay Gupta, and co‐workers. The seed of CBL that was swan 4 decades ago has enhanced the efficiency of solar cells to ≈20%, leading to ground‐breaking applications.